Kejahatan Mafia Tanah sebagai Ancaman Penguasaan Tanah yang Berkepastian Hukum - Iwan Permadi (Perspektif Hukum, 2024)
This research examines land crimes committed by the land mafia. The threat of land tenure with legal certainty due to the involvement of unscrupulous BPN officials, Notary/PPAT, village officials and the community itself makes land mafia crimes run in a planned and systematic manner. The lack of professional integrity in internal officials related to land and the attitude of honesty, trustworthiness and weak spiritual intelligence make this crime difficult to overcome. The purpose of this research is to find out the form of land mafia crime practice and the form of legal protection for its victims. This research uses normative research methods. The results show the need for good law enforcement action, both preventively (through improved regulation) and repressively (fair legal settlement in the form of sanctions and penalties) in ensuring legal protection for victims of land mafia crimes. In addition, supervision needs to be improved in the internal administration of the land programme related to the issuance of land certificates and its scope must be clear and firm. The government must dare to take firm and measurable action against officials who commit unlawful acts, both criminally and administratively, so that legal certainty and protection can be realised properly.